A Novel Homozygous Mutation ABCA3gene: Presented as Sever Respiratory Distress Syndrome in a Term Neonate (Global Journal of Medical Research, 2021)
Congenital surfactant deficiency is a rare condition diagnosed in newborns who present with respiratory distress at birth. We report a case of a term Omani neonate with fatal surfactant protein deficiency who was admitted to the Neonatal Intensive Care Unit (NICU)of the Royal Hospital with respiratory distress syndrome with persistent interstitial infiltrates on serial chest xray responsive to intermittent surfactant administration. He underwent a lung biopsy, and immunohistochemistry confirmed the diagnosis of congenital surfactant protein deficiency. However, despite aggressive treatment and supportive measures, his condition rapidly deteriorated, and he succumbed after two months of admission. This case report will highlight and review surfactant deficiency differential diagnoses, management, and complications.
Keywords: surfactant deficiency; term new-born; respiratory distress syndrome; Biopsy